PHYSICAL PROPERTIES AND CO2 SOLUBILITY OF AQUEOUS SODIUM AND POTASSIUM SALTS OF Β-ALANINE - AFTAB, ASMA (2018)
In the present work, the potential application of amino acid salts (sodium and potassium salts of β-alanine) for the bulk removal of CO2, from various industrial processes, to replace the existing conventional alkanolamines solvents were investigated. For this purpose, physical properties including density, viscosity, refractive index, and surface tension of sodium and potassium salts of β-alanine were experimentally measured for various mass fractions (0.10, 0.20, and 0.30) over a temperature range from (298.15 to 343.15) K, at atmospheric pressure.